Synthesis and Application of Circularizable Ligation Probes. (March 2001) - Myer, Sharyn E.; Day, Darren J.
We describe a PCR-based approach for the synthesis of circularizable ligation probes (CLiPs). CLiPs are single-stranded probes that consist of target-specific ends separated by a noncomplementary "linker" sequence. When hybridized to a target, the CLiP forms a nicked circle that may be sealed by DNA ligase only if the 5′ and 3′ ends show perfect Watson-Crick base pairing, thus enabling the discrimination of single nucleotide polymorphisms. Primers incorporating target sequence at their 5′ end and plasmid sequence at the 3′ end were used in a PCR amplification. In addition, the antisense primer was 5′ labeled with biotin, and the amplification was performed in the presence of fluorescently labeled dUTP. The resulting PCR product was captured with streptavidin-coated paramagnetic beads, and the top strand, which forms the CLiP, was alkali eluted. This PCR-based method has allowed the synthesis of CLiPs that are larger and more highly labeled than has previously been possible, with ligation efficiencies similar to those of the purest chemically synthesized padlock probes. Ligations performed in the presence of cognate or mismatched sequence were analyzed by denaturing PAGE using a fluorescent DNA sequencer. Genotyping using target immobilized to nylon membranes was also performed. The CLiPs were readily able to distinguish between mutant and wild-type alleles for the common genetic disorder, 21-hydroxylase deficiency. Additionally, CLiPs of different lengths were synthesized and compared.